2012
DOI: 10.1093/abbs/gms034
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid facilitates indomethacin-induced gastric ulcer healing via COX-2 up-regulation

Abstract: The mechanism of indomethacin-induced gastric ulcer healing by ellagic acid (EA) in experimental mice model is described in our study. Ulcer index (UI) and myeloperoxidase (MPO) activity of the stomach tissues showed maximum ulceration on the third day after indomethacin (18 mg/kg, single dose) administration. Preliminary observation of UI and MPO activity suggests that EA possesses ulcer-healing activity. Other anti-ulcer parameters such as the levels of prostaglandin E(2), cyclooxygenase (COX) 1 and 2 enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 50 publications
7
32
0
3
Order By: Relevance
“…Determination of extracellular and intracellular PGE 2 levels PGE 2 has been known as an important mediator of healing of gastric ulcer, dermal wound and so on (Chatterjee et al, 2012;Yamamoto et al, 2012;Choi et al, 2013;Li et al, 2011). It is reported that 15-PGDH is inhibited by a variety of pharmacological agents including NSAIDs such as indomethacin, anti-paltelet aggregatory drugs such as panaxynol (Moustafa et al, 2013;Fujimoto et al, 1998), anti-allergic drugs such as flavonoid baicalein (Iijima et al, 1980), and so on.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of extracellular and intracellular PGE 2 levels PGE 2 has been known as an important mediator of healing of gastric ulcer, dermal wound and so on (Chatterjee et al, 2012;Yamamoto et al, 2012;Choi et al, 2013;Li et al, 2011). It is reported that 15-PGDH is inhibited by a variety of pharmacological agents including NSAIDs such as indomethacin, anti-paltelet aggregatory drugs such as panaxynol (Moustafa et al, 2013;Fujimoto et al, 1998), anti-allergic drugs such as flavonoid baicalein (Iijima et al, 1980), and so on.…”
Section: Resultsmentioning
confidence: 99%
“…After acting via its PGE 2 receptor (EPR), pericellular PGE 2 is cleared via re-uptake by PG transporter (PGT) and then rapidly metabolized by cytosolic enzyme named NAD + -dependent 15-hydroxyprostaglandin dehydrogenase (15-PGDH) (Schuste, 1998). PGE 2 has been identified as an important mediator for gastric ulcer healing (Chatterjee et al, 2012;Yamamoto et al, 2012;de-Faria et al, 2012), dermal wound healing (Choi et al, 2013;Wilgus et al, 2004) and anti-fibrotic activity (Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…EA is able to accelerate healing in indomethacin GU model [32]. Thus, EA may promote GU healing by increasing collagen and FN production.…”
Section: Kotob Et Almentioning
confidence: 89%
“…EA showed the ability to potentiate healing of indomethacininduced GU in mice due to its capability to reduce neutrophils infiltration. The modulation of COX-pathway by EA helps in amplifying mucosal growth factors levels and preserving the balance of pro-/antiinflammatory cytokines levels to aggravate ulcer healing [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation